Lagging temperature problem in DTA/DSC measurement on investigation of NiTi SMA - Canbay, Canan Aksu; Karaduman, Oktay; Ozkul, Iskender (Springer, 2020)
Shape memory alloy is an essential material in the novel smart materials range. The unique properties of the material can be reacted for different inducing mediums. Every research on shape memory alloys provides a great attribute to the literature. In this work, a NiTi-based shape memory alloy was obtained in an arc melting method. The samples were sliced and kept in the furnace at 900 degrees C for homogenization. In order to make thermal characterization, DSC and DTA analyses were conducted. For the microstructural investigation, EDX and XRD measurements were taken and reported. During the measurement in DSC-DTA, the lagging temperature problem was detected and the reasons for that phenomenon are discussed.
Keywords: Shape-Memory Alloy; Transformation Behavior; Phase-Transformation; Heat-Transfer; Microstructure; Stress